Monomers, oligomers and polymers of thieno[3,4-d]thiazole - Duffy,W; Heeney,M; Mcculloch,I (2006)
Novel monomeric, oligomeric or polymeric compds. comprising one or more thieno[3,4-d]thiazole-6,4-diyl groups that are optionally substituted in 2-position, with the proviso that homopolymers of 2-nonyl-thieno[3,4-d]thiazole-6,4-diyl are excluded, are used as semiconductors or charge transport materials, in optical, electrooptical or electronic devices, and in optical, electro-optical or electronic devices comprising the novel compds. These compds. are of formula I, wherein R is in case of multiple occurrence independently of one another H, halogen, optionally substituted aryl or heteroaryl, P-Sp-, P-Sp-, or straight chain, branched or cyclic alkyl with 1 to 20 C-atoms, which is optionally mono- or polysubstituted by F, Cl, Br, I or CN, and wherein one or more non-adjacent CH2 groups are optionally replaced, in each case independently from one another, by -O-, -S-, -NH-, -NR0-, -SiR0R00-, -CO-, -COO-, -OCO-, -O-CO-O-, -S-CO-, -CO-S-, -CX1=CX2- or ethynylene in such a manner that O and/or S atoms are not linked directly to one another; R0 and R00 are independently of each other H, aryl or alkyl with 1 to 12 C-atoms; X1 and X2 are independently of each other H, F, Cl or CN; P is a polymerizable group; P is a group that can be converted to or substituted by a polymerizable group P; Sp is a spacer group or a single bond; A, B and D are independently of each other, and in case of multiple occurrence independently of one another, -CX1=CX2-, ethynylene or an arylene or heteroarylene group that is optionally substituted with one or more groups R; E is thieno[2,3d]thiazole-4,6-diyl or thieno[2,3d]thiazole-6,4-diyl that is optionally substituted in 2-position with R; a, b, c, d, e are independently of each other 0, 1, 2 or 3, with at least one of c and e being 1; n is an integer > 1; wherein the recurring units are identical or different.